Electrophysical characteristics of GaAs₁₋ₓPₓ LEDs irradiated by 2 MeV electrons - Vernydub, R.M.; Kyrylenko, O.I.; Konoreva, O.V.; Olikh, Ya.M.; Litovchenko, P.G.; Pavlovskyy, Yu.V.; Potera, P.; Tartachnyk, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
Commercial orange and yellow GaAs₁₋ₓPₓ LEDs were irradiated by 2 MeV electrons with fluences of 10¹⁴…2·10¹⁶ сm⁻², and their electrophysical characteristics were investigated in the current and voltage generators modes. It has been shown that point radiation defects introduced into GaAs₁₋ₓPₓ diodes reduce the electrical conductivity of the base. The series and parallel resistances of the device increase, compensating for the electrical conductivity of the base and reducing the probability of forming the avalanche breakdown channels. Negative differential resistance regions that appear in current-voltage characteristics are the result of the presence of a GaP sublattice in the solid solution. During irradiation, the switching voltage into the low-level state increases due to the expansion of the junction depleted region. The streamlined currents increase after irradiation, which is caused by changes in the free path length of charge carriers.